FRESH PAINT: PHOTOETHNOGRAPHY BETWEEN GRAFFITI, POETRY, AND TRANSCULTURATED VISUAL NARRATIVE - de Aguiar, Sidney Barata; Wolkoff, Gisele Giandoni (Seven Editora, 2026)
This work emphasizes a synoptic visual dimension of the city and urban art that are displayed on graffiti-covered walls, at street events, and cultural occupations that reshape the imagery of Manaus, the capital of the state of Amazonas. The aim is to expand the understanding of research with images using the technique of Photoethnography. We mainly demonstrate how the act of photographing, editing, and organizing visual series is also the work of producing theories about the city and its problems, deep contradictions, and possible solutions. The research work also aims at analyzing how street art and graffiti in the city of Manaus constitute forms of occupation and re-signification of urban space, articulating aesthetic practices in order to combat cultural erasures. We use the approach of Photoethnography to capture digital images of murals and artistic interventions spread throughout the city. A city which we perceive as organic, polyphonic, polysemantic, and full of urban art.